Aging, Non-heteronorm Conformity, and Access to a Sense of Economic Stability - Guevara, Celinne Charmaigne Angeles (Review of Women's Studies; Vol 29 No 1 (2019): Review of Women's Studies Volume XXIX, Number 1 (2019), 2023)
This study features the living conditions of 10 non-heteronorm conforming older adults residing in Batangas and Metro Manila. It examines the relationship between the respondents' experiences of gender-based discrimination and access to economic opportunities, as well as their sources of support from family or peers as they face challenges brought about by aging.